Growth Mindset and Self-Regulated Learning in College Students - Santoso, Faesol Akbar; Dwiastuti, Ike (Jurnal Sains Psikologi, 2023)
This study aims to understand the description of mindset and self-regulated learning and the correlation between the two. This study used an associative quantitative research method with quota sampling, and 590 college students in Malang City were involved. The instruments used in this study were: (1) a mindset scale (validity score of 0.343–0.704; reliability score of 0.859); and (2) a self-regulated learning scale (validity score of 0.373–0.752; reliability score of 0.865). The results of the descriptive analysis showed that out of 590 college students, 57.79 percent had a strong growth mindset, and 67.62 percent had self-regulated learning in the high category. The hypothesis test obtained a correlation coefficient of 0.593 with a significance value of 0.000, meaning a significant positive correlation exists between mindset and self-regulated learning in college students. Based on these results, it is suggested that college students can improve self-regulated learning by increasing their growth mindset. Future studies can use different research methods, such as experiments or qualitative, to learn more about mindset and self-regulated learning.